Effectiveness of Augmented Feedback on Motor Skills Performance: A Meta-Analysis - Jiménez-Díaz, Judith; Chaves-Castro, Karla; Morera-Castro, Maria (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2020)
The purpose of this study was to use the meta-analytic approach to assess the effectiveness of augmented feedback (AF) on performance and learning of motor skills. Studies were retrieved by searching electronic databases, cross refereeing, and expert criteria. Studies were selected and data was extracted by the three authors independently. The quality of the studies was measured by a modify TEXTEX scale. Random effects models using the standardized mean difference effect size (ES) were used to pool results. Risk of bias, heterogeneity, and inconsistency was examined. Twenty studies met the inclusion criteria. A total of 95 ESs were calculated, representing 949 participants. During physical practice, performance increases from pretest to acquisition when receiving AF (ES = 0.87; 95%CI = 0.65, 1.10; n = 47; I2. = 74.41; Q= 183,6; p < 0.01); while performance significantly decrease between the acquisition and retention phase after AF was removed (ES = -0.74; 95%CI = -1.04, -0.44; n = 45; I2. = 88.34; Q = 377.45; p < 0.01). Age and skill level ability of the participants, type of task, and practice characteristics, and type of feedback were analyzed as potentially moderator variables. Results suggest that AF increases performance in motor skills during physical practice, but performance decreases after removing AF in retention; all due, AF enhances learning of motor skills.